KAJIAN NILAI BUDAYA DALAM TARI RITUAL ADAT BALIATN DI SENAKIN KABUPATEN LANDAK - Anci Anci; Imma Fretisari; Winda Istiandini (Universitas Tanjungpura, 2019)
AbstractThe purpose of this research is to describe the study of cultural values contained in Baliatn traditional ritual dances in the Senakin Village, Landak district of West Kalimantan.The research focused on issues relatedto cultural values in textual and contextual studies. The research method that used in this research is descriptive research methods, qualitytative forms, and ethnochoreological approaches. Data sources are in the form of interviews. The research data are in the form of interviews and photographs.. Data collection techniques are in the form of observation, interviews, and documentation. Techniques for testing the validity of source use triangulation data. Data analysis techniques are compile and analyze. The results of this study is to show that ritual dance in Baliatn traditional ceremonies contains cultural values found in textual and contextual studies that will be linked to two basic problems of life, namelu humans with nature and human with each other. Textual aspect that can be taken are in motion, clothing, property, and the number of dancers. The contextual is seen from the dance function, which is ritual dance treatment. The result of the study expected to be a contribution in building the character of studendts in the school. Keywords:Cultural Values, Ritual Dance in Baliatn Traditional Ceremony, Senakin